PRAGMATIC FEATURES OF THE STRUCTURE “I + COGNITIVE NON-FACTIVE VERB AND EPISTEMIC ADVERB COLLOCATIONS” - Khuong, Luu Quy; Giang, Tran Thi Minh (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4281, 2018)
With 250 English examples containing the structure “I + cognitive non-factive verb and epistemic adverb collocations” from different sources such as novels, short stories and online materials, in the light of the Speech Act theory three main pragmatic features have been identified including decreasing complaining/ admonishing, giving counselling , and reducing boasting . These three pragmatic features are very helpful to learners of English in daily communication because by using the structure in his/ her utterances the speaker wants to decrease his/ her complaint or admonishment to make conversations more comfortable, give the hearer persuasive advice with his/ her own experience, and reduce boasting so that the hearer feels easy to co-operate.